P14.05 Sexual contact is the trigger! women's views and experience of the causes and triggers of bacterial vaginosis. (13th September 2015) - Bilardi, J; Walker, S; Temple-Smith, M; McNair, R; Mooney-Somers, J; Bellhouse, C; Fairley, C; Chen, M; Bradshaw, C
Abstract : Introduction: Bacterial vaginosis (BV) is a common vaginal infection, causing an abnormal vaginal discharge and/or odour in up to 50% of sufferers. Recurrence is common following recommended treatment. Increasing evidence suggests BV may be sexually transmitted, however causative agents for sexual transmission have not been verified. The aim of this study was to explore women's experiences of recurrent BV. This paper reports on findings relating to women's views and experiences around the causes and triggers of recurrent BV. Methods: Thirty five women were interviewed face-to-face or by phone about their experience of recurrent BV. Interviews took between 20–45 min. All interviews were digitally recorded, transcribed verbatim and imported into N-Vivo 9 for thematic analysis. Results: The majority of women attributed their BV episodes to some form of sexual contact or activity including unprotected sex, sex with casual partners, sex with an untreated female partner, oral sex or frequent sex. Some women reported a combination of sexual and lifestyle triggers however only a few women did not feel that some form of sexual contact had triggered their episodes of BV. While most women attributed their BV to some form of sexual contact they generally did not consider it an STI. Women used a range of self-help remedies in an attempt to treat BV symptoms and prevent further recurrences however most remedies were ineffective and at time exacerbated symptoms. Conclusion: Most women felt that their episodes of recurrent BV had been caused or triggered by some form of sexual contact. This study is one of the first studies to explore women's views and experiences around BV transmission. Further large scale studies are required to determine if women from diverse populations report similar experiences around BV transmission. Disclosure of interest statement: Dr. Jade Bilardi is in receipt of an NHMRC early career fellowship. There are no other competing interests.